2022
DOI: 10.1161/circep.121.010221
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Exercise Into Personalized Ventricular Arrhythmia Risk Prediction in Arrhythmogenic Right Ventricular Cardiomyopathy

Abstract: Background: Exercise is associated with sustained ventricular arrhythmias (VA) in Arrhythmogenic Right Ventricular Cardiomyopathy (ARVC) but is not included in the ARVC risk calculator ( arvcrisk.com ). The objective of this study is to quantify the influence of exercise at diagnosis on incident VA risk and evaluate whether the risk calculator needs adjustment for exercise. Methods: We interviewed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
(59 reference statements)
0
8
0
1
Order By: Relevance
“…Finally, our findings are consistent with the hypothesis that reduction in exercise and initiation of antiarrhythmic medications may help to reduce the likelihood of VA events. Although Bosman et al 28 examined the incremental value of adding exercise to the ARVC risk calculator and found no improvement in VA risk prediction, their analyses were restricted to risk prediction at the time of initial ARVC diagnosis. It is possible that reducing exercise and initiating antiarrhythmic medications may be important for improving individualized, longitudinal risk predictions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, our findings are consistent with the hypothesis that reduction in exercise and initiation of antiarrhythmic medications may help to reduce the likelihood of VA events. Although Bosman et al 28 examined the incremental value of adding exercise to the ARVC risk calculator and found no improvement in VA risk prediction, their analyses were restricted to risk prediction at the time of initial ARVC diagnosis. It is possible that reducing exercise and initiating antiarrhythmic medications may be important for improving individualized, longitudinal risk predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that competitive sports activity is associated with as much as a 5-fold increase in risk for SCD in young adults 25,26 and that this association is dose-dependent. 27,28 Even recreational sports contribute significantly to risk of VA and SCD. 29 In this context, our results support decreasing exercise as a plausible mechanism for reducing risk for VA. We also found that patients in our cohort were more likely to be prescribed antiarrhythmic medications at 5-year follow-up compared with at the time of initial diagnosis (Figure 2G).…”
Section: Discussionmentioning
confidence: 99%
“…The Medical Subject Headings (MeSH) terms used and combined were “Arrhythmogenic Right Ventricular Dysplasia” [Mesh] AND “Exercise” [Mesh], which resulted in 72 records. Seven animal or preclinical[ 15 16 17 18 19 20 21 ] and 18 clinical studies[ 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 ] were selected and discussed. [ Table 1 ] presents the definitions of terms used in the identified studies.…”
Section: Methodsmentioning
confidence: 99%
“…[ Table 1 ] presents the definitions of terms used in the identified studies. [ 22 23 25 26 27 28 29 30 32 33 36 ]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation